Diabe-teach: a randomized controlled trial of a gamified approach to enhance medical undergraduates’ knowledge and comprehension of diabetes mellitus - Mariam Shadan; Heba Ismail; Fathima Hana Mohamed Naushad (BMC Medical Education)
Abstract The increasing prevalence of diabetes mellitus worldwide necessitates that medical undergraduates acquire a deep understanding of the disease to ensure accurate diagnosis and effective management. Traditional teaching methods, while foundational, often lack the interactive elements that enhance student engagement and knowledge retention. This study aimed to evaluate the effectiveness of a novel educational board game, “Diabe-teach,” in enhancing knowledge retention among medical students compared with conventional self-study methods. A randomized controlled design involving 56 preclinical medical students at Dubai Medical College for Girls was used. The participants were randomly assigned to either the game-based learning group or the control group, with both groups receiving identical instructional materials on diabetes. Knowledge retention was assessed via pre- and post-test scores, whereas student engagement and perceptions were measured via a feedback survey. The results indicated that while both groups showed significant improvement in post-test scores (p < .001), the game-based group demonstrated a notably greater frequency of correct responses and a greater tendency to recognize knowledge gaps, as evidenced by the increased “I do not know” responses compared with incorrect guesses in the control group. Feedback from the game-based learning group highlighted enhanced confidence, improved communication skills, and a preference for the gamified approach over traditional methods. The findings suggest that the “Diabe-teach” board game is an effective tool for teaching complex medical concepts, fostering both knowledge retention and critical self-assessment among students. These results contribute to the growing body of literature on game-based learning, supporting its potential as a valuable adjunct to traditional medical education methods. Further research could explore the application of this approach across other medical disciplines.